CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE PRACTICES AND PERFORMANCE OF QUOTED FIRMS IN NIGERIA (Journal of Global Accounting, 2023)
The study examined the social responsibility accounting disclosure practices and performance of quoted firms in Nigeria. The study utilized the ex post facto research design. The study relied on secondary sources of data. Content analysis was used to analyze the content of annual reports and websites of the selected quoted firms. The data obtained were analyzed using t-test, Correlation and Regression analyses. The findings from the analysis revealed that there is significant difference in the level of corporate social responsibility disclosure practices between Banks and non-Bank firms in Nigeria. It also indicate a significant positive relationship between return on equity, return on total assets, firm’s size and the extent of corporate social disclosure. It was also observed that the financial performance and the size of firms play a significant role in the level of corporate social disclosure. The study recommended that a detailed and well spelt out social disclosure themes and evidence must be established to provide foundation for improving corporate social disclosures among firms. More so, the study calls for policy makers in Nigeria to imbibe social policies that are responsible for the high level of corporate social disclosure practice among non-Bank firms so as to enhance the level of social performance among Bank firms.
Keywords: Corporate Social Responsibility; Disclosure; Content analysis; Social Responsibility Accounting